Reverse Evidentiary Analysis in Article 12 B Paragraph (1) A and B of Law Number 20 of 2001 Amendments to Law Number 31 of 1999 Concerning The Eradication of Corruption - Delvin Akbar; Ariawan Gunadi (Asian Journal of Social and Humanities, 2023)
The purpose of this study is to analyze the philosophical basis of the reverse proof system for future Gratification corruption crimes and the formulation of norms for the reverse proof system for future Gratification corruption crimes. The research method used in this study is normative juridical with qualitative descriptive data analysis techniques. The results of the study are the philosophical basis of the reverse proof system for the crime of graft corruption related to bribery Article 12 B, namely that both the public prosecutor and the defendant are obliged to prove but the public prosecutor alone proves the gift received by the recipient of the gratuity while the defendant proves that the gratuity is not a bribe, has nothing to do with position and does not conflict with their duties or obligations. The construction of legal substance, which directs the formulation of reverse evidentiary norms with an emphasis on legislative policies according to the 2003 CAC as a characteristic of the combination of the hukum umum and hukum sipil legal systems as a legal system.